Multi‐view reconstruction of dynamic real‐world objects and their integration in augmented and virtual reality applications. Issue 3 (10th April 2017) - Ebner, Thomas; Feldmann, Ingo; Renault, Sylvain; Schreer, Oliver; Eisert, Peter
Abstract: We present a flexible system for high‐quality three‐dimensional reconstruction of dynamic real‐world objects based on a modular multi‐camera capture setup. The proposed algorithmic pipeline aims at the acquisition and digitization of natural and realistic representations of real people that can be easily integrated into augmented and virtual reality applications. In this context, we discuss the reduction of mesh complexity as one of the key challenges for visualizing reconstructed three‐dimensional content with augmented and virtual reality glasses and demonstrate different fields of application. Abstract : We present a flexible system for high‐quality three‐dimensional reconstruction of dynamic real‐world objects based on a modular multi‐camera capture setup. The proposed algorithmic pipeline aims at the acquisition and digitization of natural and realistic representations of real people that can be easily integrated into augmented and virtual reality applications. In this context, we discuss the reduction of mesh complexity as one of the key challenges for visualizing reconstructed three‐dimensional content with augmented and virtual reality glasses and demonstrate different fields of application.